1983
DOI: 10.1302/0301-620x.65b4.6874711
|View full text |Cite
|
Sign up to set email alerts
|

Infection after total hip replacement. With special reference to a discharge from the wound

Abstract: The risk factors associated with 34 deep infections from a consecutive series of803 total hip replacements have been analysed using standard actuarial methods. The follow-up ranged from 3 to 10 years. Absence of prophylactic antibiotics, complications after operation, discharging wounds, previous operations and remote infection were related to the development of deep periprosthetic infection. An early discharge from the wound with growth of microorganisms , though superficial in appearance, proved to be associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
0
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 5 publications
6
70
0
1
Order By: Relevance
“…As previously reported in other series the most common organisms responsible for wound infection are Staphylococcus aureus and Staphylococcus epidermidis [2,20,22]. In this series 81% of all wound infection was due to staphylococci, either in pure forms or in mixed culture with other organisms.…”
Section: Discussionsupporting
confidence: 73%
“…As previously reported in other series the most common organisms responsible for wound infection are Staphylococcus aureus and Staphylococcus epidermidis [2,20,22]. In this series 81% of all wound infection was due to staphylococci, either in pure forms or in mixed culture with other organisms.…”
Section: Discussionsupporting
confidence: 73%
“…This procedure salvaged 3 out of the 4 hip replacements with these complications in our series. A positive urinary tract culture was associated with septic arthritis, as has been reported in other series (Fitzgerald et al 1977, Surin et al 1983), although one other study did not find a significant relationship (Hill et al 1981). Usually no clear correlation can be found between the pathogens of urinary tract infections and hip septic arthritis, so a causal relationship cannot be established.…”
Section: Discussionsupporting
confidence: 52%
“…In hip arthroplasty, diabetes was associated with septic arthritis (Nelson 1987), but not always (Fitzgerald et al 1977). As in many other studies, failed fracture osteosynthesis was a risk factor for septic arthritis (Fitzgerald et al 1977, Nelson 1980, Andrews et al 1981, Surin et al 1983, Poss et al 1984. except in two large series (Salvati et al 1982, Lidwell et al 1984.…”
Section: Discussionmentioning
confidence: 66%
“…Our findings, taken together with previous studies, suggest that surgeons should think carefully before performing this elective procedure in a patient with HbA 1C C 8 or FBG C 200 mg. Although no patients in our study developed deep infection, which prevents us from evaluating the association of poor glycemic control with deep infection, previous studies reported that patients who develop superficial surgical site infection are at greater risk for deep periprosthetic joint infection [3,24,26].…”
Section: Discussionmentioning
confidence: 62%